Application of PLC Centralized Control System of Coal Mine Belt Conveyor - QIN Yong-kang; HUANG He-ping (Gong-kuang zidonghua, 2011)
In view of characteristics of long lines, multi posts and multi links of transport system of belt converyor of a mine, the paper proposed a scheme which adopts PLC centralized control system to control coal mine belt conveyor. It introduced composition, working principle and functions of PLC centralized control system. The system combines industrial television with centralized control to monitor related devices such as underground powerful belt conveyor, vibration coal feeder and coal level sensor of coal bunker, which realizes centralized control of main coal flow system. The practical application showed that the system runs well, and achieves safe and efficient running of conveyor belt.